NiCuZn Nano Ferrite Prepared by Sol Gel Method for Multilayer Chip Inductor Applications - Sujatha, Ch.; Venugopal Reddy, K.; Sowri Babu, K.; Reddy, A. Ramachandra; Rao, K.H. (Asian Journal of Chemistry, 2011)
Ni0.50Zn0.45Cu0.05Fe2O4 nanoparticles prepared through sol-gel process have been investigated by infrared spectra, X-ray diffraction analysis on the sintered samples. X-Ray diffraction patterns show single phase spinel structure. The far infrared spectra showed two absorption bands. The high frequency band ν1 and low frequency band ν2 are assigned to the tetrahedral and octahedral metal-oxygen complexes, respectively. The room temperature saturation magnetization (Ms) obtained from vibration sample magnetometer (VSM) shows Ms increases with increasing (Ms = 76.76 emu/g) sintering temperature up to 950 ºC. Initial permeability (μi) of the sintered samples increases with sintering temperature and for each sample μi is constant up to MHz frequency range showing high operating frequency of the material.